INSTITUTIONAL SUPPORT FOR FRESHWATER AQUACULTURE DEVELOPMENT-A STUDY OF MIRZAPUR DISTRICT OF UTTAR PRADESH, INDIA
The aquaculture sector has been playing an increasingly dominating role in Indian fisheries scenario since the last two and half decades. Introduction of induced breeding and composite fish culture (CFC) technologies has revolutionised the freshwater aquaculture sector in India. Institutional support has been one of the most crucial aspects in all fisheries development programmes, more so in the Indian context where most of fish farmers are socially and economically weak. The innovation of CFC technology in freshwater aquaculture sector in the early seventies generated the need for adequate and effective institutional support to farmers. Under the freshwater aquaculture development programme, the Fish Farmers Development Agencies (FFDA